Legacies of Orthodox Christianity from the Communist Period to the 21st-Century Romania - BARBA, Valentina-Monica (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2025)
This paper brings to light three instances in which the forty-two years of communism in Romania in the 20th century left lasting spiritual and existentialist legacies in the 21st century. The most important instance from a spiritual point of view is the canonisation of sixteen Romanian martyrs and witnesses of Christ who lived during the communist years in 20th-century Romania, thus constituting a spiritual legacy. The other two instances derive from the autobiographical prose poetry of Lidia Vianu, i.e., Καλειδοσκόπιο/ Kaleidoscope/ Caleidoscop and Vântul și Pescărușul/ The Wind and the Seagull/ La Mouette et le Vent .... One of them brings to the fore metanoia or the changing of the mind, constituting a propaedeutic for bettering readers’ lives. The other emanates the craving of the author to form a union with her soulmate, University Professor George Constantin Săndulescu, in the difficult circumstances of her soulmate leaving the country because of the communist regime, thus leading the author to literary digest an existentially traumatic perspective on love life. All three cases are potentially iterative as, although they originate in real biographies, they may well reverberate in the lives of other people marked by the communist years in Romania.